ANALYSIS OF CONTENT HEAVY METALS IN VARIOUS FISH SPECIES IN BATANG TORU RIVER, AEK PAHU TOMBAK AND AEK PAHU HUTAMOSU DISTRICT SOUTH TAPANULI - Sirait, Hariadi; Barus, Ternala A; Wahyuningsih, Hesti (Fakultas Perikanan dan Kelautan Universitas Riau, 2013)
Research about content of heavy metals in various fish species have been done inBatang Toru River, Aek Pahu Tombak and Aek Pahu Hutamosu district South Tapanuliin March-April 2013. The purpose of this study was to determine the content of heavymetals that accumulate in the body of fish and the water, and to determine the waterquality of River Batang Toru, Aek Pahu Tombak and Aek Pahu Hutamosu. The methodfor determining the location of sampling for fish sample is